ANALISIS IMPLEMENTASI PROGRAM ASI EKSLUSIF DI DINAS KESEHATAN KABUPATEN TAPANULI SELATAN - Fahmi, Ismail; Siregar, Yenni Farida (Universitas Aufa Royhan, 2018)
The low coverage of Exclusive breastfeeding is one of the health problems thatmust get more attention from the government, both the central government and theregional government. The coverage of Exclusive Breastfeeding in South TapanuliRegency tended to decrease in 2013 by 34.58%, in 2014 which was 14.05%, in 2015which was 22.2%. The resolution of the World Health Assembly (WHA) in 2001confirmed that child growth optimal is one of the children's rights. Implementation ofprograms to increase the use of breast milk is a priority because of the broad impact onnutritional status and health of children under five. The type of descriptive surveyresearch with a qualitative approach The informants in this study were taken purposively,namely from the South Tapanuli District Health Office namely the Secretary of the HealthOffice, Nutrition Section Head, Nutrition Section Staff, Program Planning Sub-SectionHead directly related to the Exclusive breastfeeding program. The results of healthhuman resources research in the implementation of the exclusive breastfeeding programare nutrition section officers and have multiple assignments.